ANALISIS PENERIMAAN PAJAK HOTEL TERHADAP PENINGKATAN PENDAPATAN PAJAK DAERAH DI KOTA PALU - RAFYUMAN R. MASSI, RIZKI (Fakultas Ekonomi Universitas Tadulako, 2016)
This study aims to analyze the level of growth, efficiency, effectiveness, and contribution of the hotel tax on the local tax in Palu. The data used in this study is primary and secondary tax data from 2010 until 2014. The research is conducted at the Department of Local Revenue, Finance, and Asset Management (DPPKAD) of Palu. The analytical tool used is the analysis of the growth, efficiency analysis, analysis of effectiveness, and analysis contributions. The results suggest that the growth of tax collection in Palu City is 52.73% the percentage seems to increase but the percentage fluctuates. Tax collection in Palu City in the period of 2010-2014 is very effective, which is proved that the hotel tax realization can be achieved over 100% with the level of effectiveness of 133.05%. The efficiency rate of the hotel tax is very efficient with the efficiency rate of 0.05 or 5%. Hotel tax contribution on the local tax of Palu City in 2010-2014 is 8.16%, which means that the local tax revenue of 8.61% in Palu, comes from the hotel tax.